Socio-demographic profile of patients in a clinical Peritoneal Dialysis of Sergipe, Brazil - Santos, V. S.; Abud, A. C. F.; Alves, J. A. B.; Daltro, A. S. T.; Santos, V. T. G.; Feitosa, V. L. C.; Reis, F. P. (Scientia Plena, 2012)
Peritoneal Dialysis is a method of renal replacement therapy which uses the peritoneum as a semipermeable membrane, removing solutes accumulated in the blood. The aim of study was to describe the socio-demographic profile of patients who underwent treatment for DP between January/ 2005 to December/2008 in a clinical state of Sergipe. Data were obtained from the clinic’s electronic medical record. There was a predominance of males, mulattoes, and good old school, and that hypertension and diabetes are the major co-morbidities. We conclude that meet the profile of patients is important for the planning of educational activities.